A Phonemic Analysis of Errors in Reading Arabic Texts: A Case Study of Sixth-Grade Students of Kulliyatul Mu'allimin Al-Islamiyah at Ar-Raudhatul Hasanah Islamic Boarding School - Harik Aziz Faisal; Muhammad Ridwan Hafiz Hulu; Azra Syahira Faisal; Raihan Akbarina (The Future of Education Journal, 2026)
This study was motivated by the persistent pronunciation errors made by sixth-grade students of Kulliyatul Mu'allimin Al-Islamiyah (KMI) when reading Arabic texts, particularly in Dars al-Imla', which may alter the meanings of words and sentences. The study aims to describe the causes of these reading errors, examine their forms through phonemic analysis, and explore the role of phonemic knowledge in addressing such errors. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The credibility of the findings was ensured through data triangulation. The results indicate that the reading errors were primarily caused by inadequate mastery of makharij al-huruf (articulation points of Arabic letters), limited articulation practice, and passive instructional methods. Phonemic analysis classified the errors into three categories: phoneme substitution, distortion, and deletion. Furthermore, phonemic knowledge proved effective in improving students' pronunciation accuracy and reducing reading errors.